2021
DOI: 10.3389/fphar.2021.596652
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Against Lung Cancer-New Pharmacological Insights Based on High-Throughput Metabolomics Analysis Combined with Network Pharmacology

Abstract: Andrographolide (Andro) has known to treat various illnesses such as colds, diarrhea, fever and infectious diseases. However, the effect mechanism of Andro is still unclear. Therefore, we used high-throughput metabolomics analysis to discover biomarkers, metabolic profiles and pathways to reveal the pharmacological action and effective mechanism of Andro against lung cancer. The metabolic effects of Andro on lung cancer animal was explored by ultra-performance liquid chromatography-triple-time of flight/mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Apoptosis is an energy dependent gene programmed cell death mechanism and the main way to eliminate cancer. Some studies have found that Andro has the inhibitory effect in various cancer cells, such as breast cancer ( Peng et al, 2018 ), lung cancer ( Luo et al, 2021 ), and gastric cancer ( Malat et al, 2021 ). In our study, we confirmed that Andro induces apoptosis and inhibits proliferation of PC cells both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an energy dependent gene programmed cell death mechanism and the main way to eliminate cancer. Some studies have found that Andro has the inhibitory effect in various cancer cells, such as breast cancer ( Peng et al, 2018 ), lung cancer ( Luo et al, 2021 ), and gastric cancer ( Malat et al, 2021 ). In our study, we confirmed that Andro induces apoptosis and inhibits proliferation of PC cells both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Data from The Cancer Genome Atlas Research Network (TCGA; Lung AC and Lung Squamous Cell Carcinoma Provisional sequenced tumours sample sets) were used to analyse ADSL and ATIC genetic alterations including mRNA expression z-scores (Microarray, threshold 2.0) by use of CBIPORTAL software ( , accessed on 29 June 2021). Exploration from Human genetic Atlas datasets and two public metabolomics databases from the study of Luo et al [ 33 ] and from the study of Qi et al [ 34 ] were conducted. The effect of ADSL and ATIC genetic expression on LC patient prognoses was evaluated by Kaplan–Meier survival curves of NSCLC patients with low or high mRNA expression (KMPLOTTER; , accessed on 19 June 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to growth inhibition, andrographolide could suppress aggressive metastatic cancer, including luminal-like breast cancer through NF-ĸB pathway inhibition [ 124 ]. Data from high-throughput metabolomics analysis revealed that this compound exerted its anticancer properties by enhancing immune system activity, reduces inflammation, tumor cell metastasis, and balancing visceral metabolism in a Lewis lung cancer model [ 125 ]. Resistance to cisplatin in NSCLC, achieved through autophagy, is a hindrance and andrographolide is found capable of inhibiting autophagy in cisplatin-resistant NSCLC by activating the Akt/mTOR pathway, and re-sensitizes tumor cells towards cisplatin [ 126 ].…”
Section: Natural Compounds Targeting Inflammation In Nsclcmentioning
confidence: 99%